Leader Narcissism and Ethical Context: Effects on Ethical Leadership and Leader Effectiveness. (February 2013) - Hoffman, Brian J.; Strang, Sarah E.; Kuhnert, Karl W.; Campbell, W. Keith; Kennedy, Colby L.; LoPilato, Alexander C.
The link between leader narcissism and follower perceptions of ethical leadership and leader effectiveness, including the potential moderating role of ethical context was investigated. Associations between narcissism and follower perceptions of both ethical and effective leadership were not significant. In highly ethical contexts, however, narcissistic leaders were perceived as ineffective and unethical. These results are interpreted in the context of the fit between leader personality and organizational ethical climate. Implications for research investigating the role that narcissism plays in leadership, as well as organizational responses to narcissistic leaders, are highlighted.